G20 DAN PERUBAHAN SOSIAL EKONOMI: MEMBUKA PELUANG DAN TANTANGAN TERHADAP INDONESIA - Lisa Caroline Pakpahan; Viona Francesca Purba; Sinaga, Andre Dwi Putra; Dandi Abram Situmorang; Putri Lopiga Br Tarigan; Lennai Situmorang (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This study aims to determine the impact of joining Indonesia into the international organization, namely the G20. which creates opportunities and challenges for the Indonesian state. This research uses a literature study method with a secondary data approach. The focus of this research is the opportunities and challenges experienced by Indonesia in the G20 organization. The data collection technique used in this research is to combine various sources of information such as journals, articles, books and magazines that are relevant to the topic of this research. The results of our research show that Indonesia gets many opportunities from the G20 organization, for example; opening up jobs, improving the economy, and increasing credibility or world trust in Indonesia. Then, there are several challenges faced by Indonesia in the G20 organization, for example; Increased foreign debt, internal economic inequality, and global economic dependence.